Resources for Asian studies in selected libraries in the Greater Manila Area a survey - Encarnacion, Violeta V. (1973)
This study is a survey of the five major Asian collections in the Greater Manila Area, namely, the Asian Center Library, the Ateneo de Manila University Library, the University of Santo Tomas Library, the Asian Library, and the National Library.